DETERMINASI HARGA SAHAM PERUSAHAAN JASA SUBSEKTOR PROPERTY DAN REAL ESTATE - Nur Kholifah Ihza A; Dianita Meirini (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2023)
Investors who want to invest will be careful and look for signs that the company is experiencing financial problems or is in good condition. Therefore, a financial review of the company's financial statements is needed, as well as an examination of its financial ratios. This study aims to analyze the effect of Working Capital Turn Over, Debt To Equity Ratio and Asset Growth on Share Prices of service companies in the property and ireal iestate sub-sectors listed on the Indonesia Share Prices Exchange. The sampling method used purposive sampling, in order to obtain a total of 34 companies in the research sample. The data analysis method uses multiple linear regression analysis which is processed using the SPSS 25 application. The results of the simultaneous test study show that working capital turnover, Debt To Equity Ratio and asset growth have a significant effect on share prices. The partial test shows that working capital turnover has a significant effect on share prices, debt to equity ratio has no significanti effect on share prices and asset growth has a significant effect on share prices.